A comprehensive review of current knowledge on penile squamous cell carcinoma - Thumma, Nishanth; Pitla, Neharaj; Gorantla, Vasavi; du Plessis, Maira (Frontiers in Oncology, 2024)
Neoplasm of the penis is relatively rare in most regions representing 0-2% of cancers worldwide. While the penis can be affected by sarcomas, basal cell carcinomas or even melanoma, Penile Squamous Cell Carcinoma (PSCC) represents approximately 95% of all penile neoplasms. Despite its rarity and most common presentation at later decades of life most individuals diagnosed with PSCC are faced with significant decrease in quality of life. The prevalence and incidence vary among different regions and populations, but a common trend is for diagnosis to occur late (stage 4). Underdeveloped countries are traditionally reported to have higher incidence rates; however, rates may vary significantly between urban and rural areas even in developed countries. Age adjusted rates are on the rise in some countries that used to have incidence rates of 1:100 000 or less. The list of associated risk factors is long and includes among others, lack of neonatal circumcision, poor genital hygiene, socioeconomic status, history of human papillomavirus (HPV) infection and penile intraepithelial neoplasia (PeIN). Many risk factors are widely debated among experts however HPV and PeIN are indisputable risk factors and both also form part of the classification system for PSCC. Both conditions may have occurred in the past or be present at the time of diagnosis and identifying them plays a major role in management strategies. For such a rare condition PSCC can present in many different forms clinically making diagnosis no easy feat. Diagnosis of PSCC is done through clinical examination, including lymph node palpation, followed by a biopsy, which is essential for the classification. Lymph node involvement is a common finding at first presentation and investigation of spread to deep nodes is important and can be done with the aid of PET-CT. Treatment options for PSCC include surgery, chemotherapy, and radiation therapy. Surgical removal of the tumor is considered the most effective however can lead to severe decrease of quality of life. Chemotherapy is used in the case of fixed or bulky lymph nodes, where surgery is not indicated, and for distant metastasis. Radiation therapy is particularly effective in the case of HPV-positive PSCC.